Analgesic action of hexaazaisowurtzitane derivative in somatic pain models caused by TRPA1 and TRPV1 Ion channels activation - S. G. Krylova; K. A. Lopatina; E. P. Zueva; E. A. Safonova; T. N. Povet’eva; Yu. V. Nesterova; O. G. Afanas’eva; P. V. Kul’pin; N. I. Suslov; D. A. Kulagina; S. V. Sysolyatin; V. V. Zhdanov (Бюллетень сибирской медицины, 2021)
The aim of this study was to assess the analgesic action of thiowurtzine in somatogenic nociception models by activation of TRPA1 and TRPV1 ion channels.Materials and methods. The object of the study is the compound 4-(3,4-dibromothiophenecarbonyl)-2,6,8,12-tetraacetyl-2,4,6,8,10,12-hexaazatetracyclo [5.5.0.03,11.05,9]dodecane (thiowurtzine). The analgesic activity of thiowurtzine was studied under the conditions of a chemogenic activation model of TRPA1 channels (by the formalin test), and by a selective test with an agonist of TRPV1 channels (the capsaicin test). The compound was administered once per os in a dose range of 50–200 mg/kg (water-tween solvent) an hour before the experimental manipulations. The reference drugs were diclofenac sodium in a preventive single per os dose of 10 mg/kg in 1% starch gel in a volume of 0.2 ml/mouse, and ketorolac in a dose of 6 mg/kg in the same solvent, volume and route of administration.Results. Thiowurtzine, when administered in per os doses of 100 and 200 mg/kg, was found to effectively block nociceptive reactions caused by activation of TRPA1 and TRPV1 ion channels. At the same time, the analgesic activity of thiowurtzine turned out to be comparable and/(or) superior to the ketorolac and diclofenac action, depending on the model situation. In addition, it was found that thiowurtzine (200 mg/kg per os) corresponds to diclofenac sodium (10 mg/kg per os) and is superior to ketorolac (6 mg/kg per os) in terms of anti-inflammatory severity in the formalin test.Conclusion. The biphasicity of behavioral reactions in the prognostic formalin test do not allow for an unambiguous conclusion about the direction of the action mechanism of thiowurtzine, which confirms the polymodality hypothesis. The data obtained in the two models of somatogenic nociception do not exclude the fact that the modulation of the TRPA1 and TRPV1 activity is one of the mechanisms of the thiowurtzine analgesic action. By the key analgesic characteristics found herein, thiowurtzine proves to be a unique compound with a high therapeutic and innovation potential.